APLIKASI PEMBELAJARAN SHALAT MENURUT AS-SUNNAH BERBASIS ANDROID DENGAN METODE QUANTUM LEARNING - Ramli -; Dody Hidayat; Joko Suprianto (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2018)
Prayer is one of worship obligatory for every muslim, started from children to adults are required to be able to pray properly. However, sometimes children are often forgotten or confused in reading and prayer movement. Therefore, the authors build a learning application along with the five daily prayers prayer position drawing, reading prayers, reading the meaning of prayer and equipped with sound for each reading, and there is a collection of daily prayers and ablutions ordinances. Applications built prayer is android-based application that can be accessed using a mobile phone that is user friendly with an attractive appearance so as to increase the interest of children and adolescents in the study according to the As-Sunnah prayer. This application created using Eclipse software with the Java programming language using Quantum Learning methods.